Pounding Rice, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A woman of East Indian descent, outside of a mud hut pounding rice while a young child looks on. Postcard number 25566.
Colour: Black and white; Style: Portrait; Other: Bordered, Divided
Keywords: Postcards; Trinidad and Tobago; Rice--Milling--Trinidad and Tobago; Grain--Milling--Trinidad and Tobago; Children--Trinidad and Tobago; East Indians--Trinidad and Tobago; Women--Trinidad and Tobago; Bracelets--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Food--Trinidad and Tobago; Huts--Trinidad and Tobago; Mortars--Trinidad and Tobago; Pestles--Trinidad and Tobago; Implements, utensils, etc.--Trinidad and Tobago; [1930]